Oral Health Status of Syrian Children in the Refugee Center of Melilla, Spain - Sabrina Gonçalves Riatto; Javier Montero; David Ribas Pérez; Antonio Castaño-Séiquer; Abraham Dib (Hindawi Limited, 2018)
Introduction. Little is known about the state of oral health among immigrants from conflict zones, such as the refugee children from the Syrian Civil War. Aim. To determine the oral health status of Syrian immigrant children refugee at the Center for Temporary Stay of Immigrants in Melilla to plan prevention and care programs. Design. Using the criteria set by the World Health Organization, an exploration of the oral cavity of all Syrian children aged 5-13 living at that center was conducted in May 2015. All subjects were clinically evaluated by a calibrated and standardized examiner, accompanied by a dentist who registered the clinical variables, and translators. The sociodemographic and clinical variables were analyzed through a descriptive and analytical study, respectively. Results. The prevalence of caries in both the permanent and deciduous dentition was 75% and 50% in 6- and 12-year-olds, respectively. The dft was 3.2 ± 2.9 in 6-year-old children. At 12 years old, the DMFT was 1.6 ± 2.6 teeth, the DMFM was 1.1 ± 1.7 teeth, the SiC was 3.2, and the IR was 5%. Eighty-six percent of the examined sextants were periodontally healthy. Conclusions. The prevalence of caries was high in the sample population studied, confirming the need for a comprehensive primary oral health care program.